Tantangan Penggunaan Aplikasi ELSIMIL Bagi Calon Pengantin di Kecamatan Kasemen Kota Serang - Indri Astuti, Ismaya; Ropika Dana Br Tarigan, Sri; Stiawati, Titi (Policy, Law and Political Research Center, 2025)
The Indonesian government has developed the Elektronik Siap Nikah dan Hamil (ELSIMIL) application as a digital innovation to prepare prospective brides and grooms (Catin) in facing healthy marriages and pregnancies and preventing the risk of stunting in children. This application is part of the digital transformation effort in supporting the national program, in accordance with the mandate of Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction. However, the implementation of the ELSIMIL application in the community faces various challenges, such as the digital divide, low technological literacy, cultural resistance to reproductive health issues, and concerns about the security of personal data. This study uses a descriptive qualitative method to explore the technical, social, and cultural challenges in using the ELSIMIL application in Kasemen District, Serang Regency. Data were collected through observation, interviews, and documentation from three informants consisting of TPK, PKK, and KB cadres. The results of the study indicate that limited digital infrastructure, low technological literacy, and cultural resistance are the main obstacles to the use of the application. Community-based socialization, direct technical assistance, and transparency in user data management are recommended as solutions to increase the adoption of this application.